Pd / SCM-1 molecular sieve catalyst as well as preparation method and application thereof
By loading Pd metal nanoparticles using atomic layer deposition technology on SCM-1 molecular sieve, the problems of poor metal dispersion and low selectivity of cyclohexylbenzene on the molecular sieve were solved, and cyclohexylbenzene production was achieved with high selectivity and yield.
Patent Information
- Application Number
- CN202310781131.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-06-28
AI Technical Summary
In the prior art, the metals supported on the molecular sieve have poor dispersion uniformity, large metal particle size, and low selectivity of cyclohexylbenzene in benzene hydroalkylation reaction.
Pd/SCM-1 molecular sieve catalyst is used to load Pd metal nanoparticles on the molded SCM-1 molecular sieve through atomic layer deposition technology, and the particle size is controlled to be 2-4 nm to improve metal dispersion and selectivity.
The production of cyclohexylbenzene with high selectivity and yield is achieved, and through the use of ALD technology, the uniform distribution and small particle size of metal particles are ensured, and the universality of the catalyst is enhanced.
Smart Images

Figure CN119237001A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst synthesis, and in particular to a Pd / SCM-1 molecular sieve catalyst and a preparation method and catalytic application thereof. Background Art
[0002] Phenol and cyclohexanone are important industrial raw materials. Currently, they are mostly prepared by cumene and cyclohexane oxidation, which has the disadvantages of high energy and material consumption and serious environmental pollution. The green new method of synthesizing cyclohexylbenzene by benzene hydrogenation alkylation, further oxidation and decomposition to simultaneously produce two high value-added products, phenol and cyclohexanone, has received great attention. Cyclohexylbenzene can also be used as an additive to lithium-ion battery electrolyte to improve the battery's anti-overcharge performance. With the scale-up of cyclohexylbenzene oxidation technology to phenol and the rise of the electric revolution, the preparation and production of cyclohexylbenzene has great theoretical research value and industrial application prospects. The bifunctional supported metal / molecular sieve catalyst formed by combining zeolite molecular sieves with excellent acidity with metals is one of the most valuable catalysts for this reaction.
[0003] Patents US3839477 and US4177165 disclose catalysts loaded with precious metals on X or Y type molecular sieves, respectively, and apply them to benzene hydroalkylation reaction, but the conversion rate of benzene and the selectivity of cyclohexylbenzene are low. Patents US5054571, US5146024, US6037513, CN101687728A, CN101754940A, CN101796000A, CN101925561A, CN101754940A, and CN103261126A report methods for preparing hydroalkylation catalysts by loading at least one metal (Pt, Pd, Ru, Ir) on molecular sieves, mainly using impregnation and ion exchange as the main means, and there is a problem of uneven distribution of metal particle size, and the selectivity of cyclohexylbenzene of the obtained catalyst needs to be further improved.
[0004] CN114130421A discloses a bifunctional catalyst applied to benzene hydroalkylation reaction, and the preparation method of the catalyst is to react a metal component with a specific inorganic / organic ligand to form a specific complex, adjust the acidity and alkalinity of the solution, and then mix it with the reaction raw materials of the synthetic molecular sieve, and then crystallize it by reaction to obtain a metal / molecular sieve catalyst. Although the method obtains a catalyst by a "one-pot method", due to the metal complex introduced during the synthesis of the molecular sieve, there is an unknown influence on the molding of the molecular sieve framework, and the mechanism of metal nucleation process is difficult to understand and lacks certain controllability. In addition, since in this method, the noble metal precursor is introduced during the molecular sieve crystallization molding process, rather than metal loading on the molecular sieve after molding, the metal particle size is seriously dependent on the properties of the molecular sieve itself and cannot be controlled by regulating the synthesis process of the metal alone.
[0005] In summary, how to further develop a metal loading method for molecular sieves with high metal dispersion, small and uniform particle size to improve the selectivity of cyclohexylbenzene is the key to research in this field. Summary of the invention
[0006] The technical problem to be solved by the present invention is that the metal loaded on the molecular sieve in the prior art has poor dispersion uniformity, large metal particle size, and poor selectivity of cyclohexylbenzene in the benzene hydroalkylation reaction. The present invention provides a Pd / SCM-1 molecular sieve catalyst and a preparation method and application thereof. The catalyst of the present invention has the characteristics of high metal dispersion, small and uniform particle size. The Pd / SCM-1 molecular sieve catalyst of the present invention is used in the reaction of preparing cyclohexylbenzene by benzene hydroalkylation, and has good selectivity and yield of cyclohexylbenzene.
[0007] The first aspect of the present invention provides a Pd / SCM-1 molecular sieve catalyst, which comprises an SCM-1 molecular sieve and a metal component Pd. On the surface of the catalyst, Pd metal particles with a particle size of 2 to 4 nm account for more than 85% of all Pd metal particles.
[0008] Furthermore, in the SCM-1 molecular sieve, the crystals are in nano-sheet morphology, and the average thickness of the crystals is not higher than 15 nm, preferably 2 to 12 nm, and more preferably 8 to 10 nm.
[0009] Furthermore, the external specific surface area of the SCM-1 molecular sieve is not less than 150m 2 / g, preferably 150 to 250 m 2 / g.
[0010] Furthermore, in the catalyst, based on the weight of the catalyst, the content of the metal component Pd as an element is 0.01% to 5.0%, preferably 0.1% to 2.0%, and the rest is SCM-1 molecular sieve.
[0011] Furthermore, on the catalyst surface, metal Pd particles with a particle size of 2.5 to 3.5 nm account for more than 90% of all Pd metal particles.
[0012] The second aspect of the present invention provides a method for preparing the above-mentioned Pd / SCM-1 molecular sieve catalyst, comprising the following steps:
[0013] (1) palladium source vapor contacts with SCM-1 molecular sieve for reaction;
[0014] (2) purging the product obtained in step (1) for the first time with an inert gas;
[0015] (3) contacting the product after purging in step (2) with a reducing agent to react;
[0016] (4) The product obtained in step (3) is purged for a second time with an inert gas to obtain the Pd / SCM-1 molecular sieve catalyst.
[0017] Furthermore, the preparation method of the Pd / SCM-1 molecular sieve catalyst is carried out in a closed chamber atomic layer deposition reactor (ALD).
[0018] Furthermore, the number of deposition cycles of Pd ALD is one cycle, that is, step (1) to step (4) is one deposition cycle.
[0019] Further, the palladium source vapor in step (1) is obtained by heating the palladium source to 55-80° C., preferably 60-70° C. The palladium source vapor is introduced into the reactor using a carrier gas. Further, the carrier gas is preferably high-purity nitrogen, and the purity is preferably 99.999v% or more. In step (1), the flow rate of the carrier gas is 5-50mL / min, preferably 10-30mL / min, relative to 1-3g SCM-1 molecular sieve.
[0020] Furthermore, in step (1), the reaction temperature is 80 to 300°C, preferably 120 to 250°C.
[0021] Furthermore, in step (1), the reaction time is no longer than 2000 seconds, preferably 800 to 1800 seconds, and more preferably 800 to 1200 seconds.
[0022] Furthermore, in step (1), the palladium source is at least one of bis(hexafluoroacetylacetonate)palladium (Pd(hfac)2), (2,2,6,6-tetramethyl-3,5-heptanedione)palladium, and acetylacetonate palladium.
[0023] Furthermore, in step (2) or step (4), the inert gas is preferably high-purity nitrogen, and the purity is preferably above 99.999v%.
[0024] Furthermore, in step (2), the first purge time is 500 to 800 seconds.
[0025] Furthermore, in step (3), the reducing agent is at least one of formaldehyde and hydrogen.
[0026] Furthermore, in step (3), the reaction time is no longer than 2000 seconds, preferably 800 to 1800 seconds, and more preferably 800 to 1200 seconds.
[0027] Furthermore, in step (4), the second purge time is 500 to 800 seconds.
[0028] Furthermore, the preparation method of the SCM-1 molecular sieve comprises the following steps:
[0029] The SCM-1 molecular sieve is prepared by mixing a silicon source, an aluminum source, an alkali source, an organic structure directing agent I, an organic structure directing agent II and water, crystallizing and calcining.
[0030] Furthermore, the organic structure directing agent I is hexamethyleneimine (HMI), and the organic structure directing agent II is dicyclohexylamine (DCHA).
[0031] Furthermore, the aluminum source is selected from at least one of sodium aluminate and aluminum isopropoxide, preferably sodium aluminate; the silicon source is selected from at least one of silica sol and tetraethyl silicate, preferably silica sol; and the alkali source is selected from at least one of sodium hydroxide and potassium hydroxide, preferably sodium hydroxide.
[0032] Furthermore, the silicon source is calculated as SiO2, and the aluminum source is calculated as Al2O3, and the molar ratio of each material is: SiO2: Al2O3: NaOH: organic structure directing agent I: organic structure directing agent II: H2O = 1: 0.020-0.060: 0.08-0.15: 0.15-0.35: 0.2-0.6: 10-40, preferably SiO2: Al2O3: NaOH: organic structure directing agent I: organic structure directing agent II Structure directing agent II: H2O=1: 0.025-0.040: 0.09~0.13: 0.20~0.30: 0.3~0.5: 18~33; further preferred is SiO2: A12O3: NaOH: organic structure directing agent I: organic structure directing agent II: H2O=1: 0.025-0.040: 0.09~0.13: 0.20~0.30: 0.30~0.50: 22~33.
[0033] Furthermore, the crystallization temperature of SCM-1 molecular sieve is 140-170° C., preferably 145-155° C.; the crystallization time is 1-5 days, preferably 3-4 days.
[0034] Furthermore, the calcination temperature is 450-650° C., preferably 500-600° C., the calcination time is 4-8 hours, preferably 5-6 hours, and the calcination atmosphere is air.
[0035] Furthermore, the SCM-1 molecular sieve described in step (1) is a hydrogen-type molecular sieve. Generally, the SCM-1 molecular sieve can be a hydrogen-type molecular sieve directly obtained during preparation, or a sodium-type or potassium-type molecular sieve can be converted into a hydrogen-type SCM-1 molecular sieve by a conventional ammonium exchange method.
[0036] The third aspect of the present invention also provides the use of the Pd / SCM-1 molecular sieve catalyst described in any one of the first aspects or the Pd / SCM-1 molecular sieve catalyst prepared according to any one of the preparation methods described in the second aspect in the catalytic reaction of benzene hydroalkylation.
[0037] Furthermore, the reaction conditions are: reaction temperature of 100-250° C., hydrogen pressure of 1.0-4.0 MPa, hydrogen / benzene molar ratio of 0.5-2.0, and benzene / catalyst mass ratio of 40-60.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] (1) In the Pd / SCM-1 molecular sieve catalyst of the present invention, the SCM-1 molecular sieve crystals have a nano-sheet morphology, and the thickness of the crystals is not more than 15 nm. The two-dimensional morphology, high specific surface area and narrow thickness distribution of the molecular sieve material are conducive to the uniform distribution of the metal precursor, and then the metal Pd nanoparticles with small particle size and narrow distribution are loaded through atomic layer deposition (ALD).
[0040] (2) Small-sized metals tend to aggregate during the synthesis process, so the smaller the particle size, the more difficult it is to obtain a narrower particle size distribution. The present invention uses atomic layer deposition technology to load Pd metal nanoparticles on a SCM-1 molecular sieve with a specific two-dimensional structure in a gas phase method under suitable reaction conditions. The Pd particles synthesized by this method have uniform particle size and high dispersion. Pd metal particles with a particle size of 2 to 4 nm account for more than 85% of all Pd metal particles, and preferably Pd metal particles with a particle size of 2.5 to 3.5 nm account for more than 90% of all Pd metal particles. In addition, this method can be carried out on a formed molecular sieve and has high universality.
[0041] (3) The Pd / SCM-1 molecular sieve catalyst prepared by the present invention is applied to the catalytic reaction of benzene hydroalkylation and shows high selectivity. Under suitable reaction conditions, the selectivity of cyclohexylbenzene is not less than 45%, and the selectivity of cyclohexane is not more than 55%. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is the X-ray diffraction spectrum of the SCM-1 molecular sieve obtained in Example 1;
[0043] Figure 2 This is a transmission electron microscope image of the Pd / SCM-1 molecular sieve catalyst obtained in Example 1;
[0044] Figure 3 is a transmission electron microscope image of the catalyst obtained in Comparative Example 2;
[0045] Figure 4 is a transmission electron microscope image of the catalyst obtained in Comparative Example 3;
[0046] Figure 5 This is the X-ray diffraction spectrum of the molecular sieve sample obtained in Comparative Example 1. DETAILED DESCRIPTION
[0047] In the context of this specification, including the following examples and comparative examples, the molecular sieve X-ray powder diffractometer model is Panalytical X PERPRO X-ray powder diffractometer, the phase of the sample is analyzed, and the CuKα ray source is Nickel filter, 2θ scanning range 2~50°, operating voltage 40KV, current 40mA, scanning rate 10° / min.
[0048] In the context of this specification, including in the following examples and comparative examples, the method for measuring the crystal thickness of the molecular sieve is: using a transmission electron microscope (G2F30 transmission electron microscope of FEI Company of the Netherlands, working voltage 300kV) to observe the molecular sieve at a magnification of 100,000 times, randomly selecting an observation field of view, measuring the thickness of all crystals in the observation field of view, repeating the operation 5 times, and taking the average value of the 5 times as the average thickness of the crystal.
[0049] In the context of this specification, including in the following examples and comparative examples, the method for measuring the particle size of Pd metal particles is: using a transmission electron microscope (G2F30 transmission electron microscope from FEI Company of the Netherlands, working voltage 300kV) to observe the catalyst at a magnification of 100,000 times, randomly selecting an observation field of view, measuring the size of all Pd particles in the observation field of view, statistically counting samples greater than 100, and then averaging the obtained particle size values.
[0050] In the context of this specification, the loading amount of Pd metal supported on the catalyst is characterized by inductively coupled plasma optical emission spectroscopy (ICP-OES). The valence state of Pd metal is characterized by X-ray photoelectron spectroscopy (XPS).
[0051] In the context of this specification, the reaction products benzene, cyclohexane, cyclohexylbenzene, dicyclohexylbenzene, etc. are analyzed by gas chromatography (GC). The gas chromatograph is Agilent 7890B, the detector is a hydrogen flame ionization detector (FID), and the chromatographic column is a SE-54 capillary column (30m, 0.53mm).
[0052] In the context of this specification, when calculating the product selectivity and cyclohexylbenzene yield, the amount of each substance is based on mass.
[0053] In order to facilitate the understanding of the present invention, the present invention lists the following embodiments, but the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0054] [Example 1]
[0055] Take a reaction container, add 21.08g of water, add 0.21g of 10wt% sodium hydroxide solution under stirring, then add 1.09g of hexamethyleneimine, 3.17g of dicyclohexylamine, 0.367g of sodium aluminate, and 6.07g of silica sol, and then continue stirring at room temperature for 3 hours to obtain a mixture. The final material ratio (molar ratio) is:
[0056] SiO2 / Al2O3=30;
[0057] NaOH / SiO2=0.09;
[0058] Hexamethyleneimine / SiO2=0.25;
[0059] Dicyclohexylamine / SiO2=0.40;
[0060] H2O / SiO2=32.
[0061] After the reaction materials are evenly mixed, they are transferred to a stainless steel reactor and crystallized at 150°C for 72 hours under stirring. After the crystallization reaction is completed, wash with deionized water several times until the pH value of the washing liquid reaches neutral, then dry at 80°C for 24 hours, and then transfer to a muffle furnace and calcine at 550°C in an air atmosphere for 6 hours to obtain a sodium-type SCM-1 molecular sieve. The sodium-type SCM-1 molecular sieve is exchanged with 0.5 mol / L NH4Cl solution at 45°C for ammonium ions for 2 hours, then centrifuged and washed. The ammonium ion exchange is repeated three times, and the obtained sample is dried at 80°C overnight, and calcined in air at 550°C for 6 hours to obtain a hydrogen-type SCM-1 molecular sieve sample A, whose X-ray diffraction spectrum is shown in Figure 1 .
[0062] A closed chamber atomic layer deposition reactor (ALD) was used to perform PdALD at 150°C with bis(hexafluoroacetylacetonate)palladium (Pd(hfac)2) and formaldehyde solution as reaction precursors. High-purity N2 (99.999%) was used as the carrier gas with a flow rate of 30 mL / min. During the experiment, the Pd precursor source bottle was heated to 65°C to achieve sufficient vapor pressure, the air inlet was maintained at 115°C, and the chamber was heated to 150°C to prevent the precursor from condensing. In the catalyst preparation process, specifically, 2g of SCM-1 molecular sieve powder A is placed in the reaction chamber, (1) Pd(hfac)2 vapor is introduced into the reaction chamber using high-purity N2 gas to react with the SCM-1 molecular sieve powder for 900 seconds; (2) After the Pd(hfac)2 source is turned off, it is purged with high-purity N2 gas to remove unreacted Pd(hfac)2 precursor and precursor molecular fragments after the reaction for 600 seconds; (3) The formaldehyde solution source bottle is opened and introduced into the reaction chamber for 900 seconds; (4) After the formaldehyde source is turned off, it is purged with high-purity N2 gas for 600 seconds. The above steps (1)-(4) are referred to as one atomic layer deposition cycle. After one atomic layer deposition cycle is completed, the sample is taken out from the reaction chamber to obtain catalyst A.
[0063] The high-angle annular dark-field scanning transmission electron microscopy results of the obtained catalyst A ( Figure 2 ) It can be seen that the Pd nanoparticles are highly dispersed on the molecular sieve, and the Pd metal particles with a particle size of 2.5-3.5 nm account for 95% of all the Pd metal particles. The Pd metal loading measured by ICP-OES is 0.2wt.%.
[0064] [Example 2]
[0065] Take a reaction container, add 18.33g of water, add 0.26g of 10wt% sodium hydroxide solution under stirring, then add 1.66g of hexamethyleneimine, 3.93g of dicyclohexylamine, 0.405g of sodium aluminate, and 8.16g of silica sol, and then continue stirring at room temperature for 3 hours to obtain a mixture. The final material ratio (molar ratio) is:
[0066] SiO2 / Al2O3=30;
[0067] NaOH / SiO2=0.09;
[0068] Hexamethyleneimine / SiO2=0.25;
[0069] Dicyclohexylamine / SiO2=0.40;
[0070] H2O / SiO2=24.
[0071] After the reaction materials are mixed evenly, they are transferred to a stainless steel reactor and crystallized at 150°C for 72 hours under stirring. After the crystallization reaction is completed, it is washed with deionized water several times until the pH value of the washing liquid reaches neutral, and then dried at 80°C for 24 hours, and then transferred to a muffle furnace and calcined at 550°C in an air atmosphere for 6 hours to obtain a sodium-type SCM-1 molecular sieve. The sodium-type SCM-1 molecular sieve is exchanged with 0.5 mol / L NH4Cl solution at 45°C for ammonium ions for 2 hours, and then centrifuged and washed. The ammonium ion exchange is repeated three times, and the obtained sample is dried at 80°C overnight, and calcined in air at 550°C for 6 hours to obtain a hydrogen-type SCM-1 molecular sieve sample B, whose X-ray diffraction spectrum is similar to Figure 1 .
[0072] The SCM-1 molecular sieve powder B was prepared by the same ALD metal deposition method as in Example 1 to obtain catalyst B.
[0073] In the obtained catalyst B, Pd nanoparticles are highly dispersed on the molecular sieve, and Pd metal particles with a particle size of 2.5-3.5 nm account for 91% of all Pd metal particles. ICP-OES measured the Pd metal loading to be 0.2 wt.%.
[0074] [Example 3]
[0075] Take a reaction container, add 20.5g of water, add 0.22g of 10wt% sodium hydroxide solution under stirring, then add 1.15g of hexamethyleneimine, 3.33g of dicyclohexylamine, 0.386g of sodium aluminate, and 6.91g of silica sol, and then continue stirring at room temperature for 3 hours to obtain a mixture. The final material ratio (molar ratio) is:
[0076] SiO2 / Al2O3=30;
[0077] NaOH / SiO2=0.09;
[0078] Hexamethyleneimine / SiO2=0.25;
[0079] Dicyclohexylamine / SiO2=0.40;
[0080] H2O / SiO2=30.
[0081] After the reaction materials are mixed evenly, they are transferred to a stainless steel reactor and crystallized at 150°C for 72 hours under stirring. After the crystallization reaction is completed, it is washed with deionized water several times until the pH value of the washing liquid reaches neutral, and then dried at 80°C for 24 hours, and then transferred to a muffle furnace and calcined at 550°C in an air atmosphere for 6 hours to obtain a sodium-type SCM-1 molecular sieve. The sodium-type SCM-1 molecular sieve is exchanged with 0.5 mol / L NH4Cl solution at 45°C for ammonium ions for 2 hours, and then centrifuged and washed. The ammonium ion exchange is repeated three times, and the obtained sample is dried at 80°C overnight, and calcined in air at 550°C for 6 hours to obtain a hydrogen-type SCM-1 molecular sieve sample C, whose X-ray diffraction spectrum is similar to Figure 1 .
[0082] The SCM-1 molecular sieve powder C was prepared by the same method as in Example 1 for depositing metal by ALD to obtain catalyst C.
[0083] In the obtained catalyst C, the Pd nanoparticles are highly dispersed on the molecular sieve, and the Pd metal particles with a particle size of 2.5-3.5 nm account for 93% of all the Pd metal particles. The Pd metal loading measured by ICP-OES is 0.2 wt.%.
[0084] [Example 4]
[0085] Take a reaction container, add 15.21g of water, add 0.32g of 10wt% sodium hydroxide solution under stirring, then add 1.66g of hexamethyleneimine, 4.80g of dicyclohexylamine, 0.556g of sodium aluminate, and 9.95g of silica sol, and then continue stirring at room temperature for 3 hours to obtain a mixture. The final material ratio (molar ratio) is:
[0086] SiO2 / Al2O3=30;
[0087] NaOH / SiO2=0.09;
[0088] Hexamethyleneimine / SiO2=0.25;
[0089] Dicyclohexylamine / SiO2=0.40;
[0090] H2O / SiO2=18.
[0091] After the reaction materials are mixed evenly, they are transferred to a stainless steel reactor and crystallized at 150°C for 72 hours under stirring. After the crystallization reaction is completed, the mixture is washed with deionized water several times until the pH value of the washing liquid reaches neutrality, and then dried at 80°C for 24 hours, and then transferred to a muffle furnace and calcined at 550°C in an air atmosphere for 6 hours to obtain a sodium-type SCM-1 molecular sieve. The sodium-type SCM-1 molecular sieve is exchanged with 0.5 mol / L NH4Cl solution at 45°C for ammonium ions for 2 hours, and then centrifuged and washed. After repeating the ammonium ion exchange three times, the obtained sample is dried at 80°C overnight and calcined in air at 550°C for 6 hours to obtain a hydrogen-type SCM-1 molecular sieve sample D.
[0092] The SCM-1 molecular sieve powder D was prepared by the same method as in Example 1 for depositing metal by ALD to obtain catalyst D.
[0093] In the obtained catalyst D, the Pd metal particles with a particle size of 2.5-3.5 nm accounted for 85% of all the Pd metal particles. The Pd metal loading was measured by ICP-OES to be 0.2 wt.%.
[0094] [Example 5]
[0095] Take a reaction container, add 21.08g of water, add 0.20g of 10wt% sodium hydroxide solution under stirring, then add 1.07g of hexamethyleneimine, 3.10g of dicyclohexylamine, 0.358g of sodium aluminate, and 6.41g of silica sol, and then continue stirring at room temperature for 3 hours to obtain a mixture. The final material ratio (molar ratio) is:
[0096] SiO2 / Al2O3=30;
[0097] NaOH / SiO2=0.09;
[0098] Hexamethyleneimine / SiO2=0.25;
[0099] Dicyclohexylamine / SiO2=0.4;
[0100] H2O / SiO2=33.
[0101] After the reaction materials are mixed evenly, they are transferred to a stainless steel reactor and crystallized at 150°C for 72 hours under stirring. After the crystallization reaction is completed, it is washed with deionized water several times until the pH value of the washing liquid reaches neutral, and then dried at 80°C for 24 hours, and then transferred to a muffle furnace and calcined at 550°C in an air atmosphere for 6 hours to obtain a sodium-type SCM-1 molecular sieve. The sodium-type SCM-1 molecular sieve is exchanged with 0.5 mol / L NH4Cl solution at 45°C for ammonium ions for 2 hours, and then centrifuged and washed. The ammonium ion exchange is repeated three times, and the obtained sample is dried at 80°C overnight, and calcined in air at 550°C for 6 hours to obtain a hydrogen-type SCM-1 molecular sieve sample E, whose X-ray diffraction spectrum is similar to Figure 1 .
[0102] The SCM-1 molecular sieve powder E was prepared by the same method as in Example 1 where metal was deposited by ALD to obtain catalyst E.
[0103] In the obtained catalyst E, the Pd nanoparticles were highly dispersed on the molecular sieve, and the Pd metal particles with a particle size of 2.5-3.5 nm accounted for 94% of all the Pd metal particles. The Pd metal loading measured by ICP-OES was 0.2 wt.%.
[0104] [Example 6]
[0105] The preparation of hydrogen-type SCM-1 molecular sieve is the same as in Example 1.
[0106] A closed chamber atomic layer deposition reactor (ALD) was used to perform PdALD at 150°C with bis(hexafluoroacetylacetonate)palladium (Pd(hfac)2,) and formaldehyde solution as reaction precursors. High-purity N2 (99.999%) was used as the carrier gas with a flow rate of 30 mL / min. During the experiment, the Pd precursor source bottle was heated to 65°C to achieve sufficient vapor pressure, the air inlet was maintained at 115°C, and the chamber was heated to 150°C to prevent the precursor from condensing. In the catalyst preparation process, specifically, 2g of SCM-1 molecular sieve powder is placed in the reaction chamber, (1) Pd(hfac)2 vapor is introduced into the reaction chamber using high-purity N2 gas to react with the SCM-1 molecular sieve powder for 1400 seconds; (2) After the Pd(hfac)2 source is turned off, it is purged with high-purity N2 gas to remove unreacted Pd(hfac)2 precursor and precursor molecular fragments after the reaction for 600 seconds; (3) The formaldehyde solution source bottle is opened and introduced into the reaction chamber for 1400 seconds; (4) After the formaldehyde source is turned off, it is purged with high-purity N2 gas for 600 seconds. The above steps (1)-(4) are referred to as one atomic layer deposition cycle. After one atomic layer deposition cycle is completed, the sample is taken out from the reaction chamber to obtain catalyst F.
[0107] In the obtained catalyst F, the Pd nanoparticles were highly dispersed on the molecular sieve, and the Pd metal particles with a particle size of 2.5-3.5 nm accounted for 91% of all the Pd metal particles. The Pd metal loading measured by ICP-OES was 0.3 wt.%.
[0108] [Example 7]
[0109] The preparation of hydrogen-type SCM-1 molecular sieve is the same as in Example 1.
[0110] A closed chamber atomic layer deposition reactor (ALD) was used to perform PdALD at 150°C with bis(hexafluoroacetylacetonate)palladium (Pd(hfac)2,) and formaldehyde solution as reaction precursors. High-purity N2 (99.999%) was used as the carrier gas with a flow rate of 30 mL / min. During the experiment, the Pd precursor source bottle was heated to 65°C to achieve sufficient vapor pressure, the air inlet was maintained at 115°C, and the chamber was heated to 150°C to prevent the precursor from condensing. In the catalyst preparation process, specifically, 2g of SCM-1 molecular sieve powder is placed in the reaction chamber, (1) Pd(hfac)2 vapor is introduced into the reaction chamber using high-purity N2 gas to react with the SCM-1 molecular sieve powder for 1300 seconds; (2) After the Pd(hfac)2 source is turned off, it is purged with high-purity N2 gas to remove unreacted Pd(hfac)2 precursor and precursor molecular fragments after the reaction for 600 seconds. (3) The formaldehyde solution source bottle is opened and introduced into the reaction chamber for 1800 seconds; (4) After the formaldehyde source is turned off, it is purged with high-purity N2 gas for 600 seconds. The above steps (1)-(4) are referred to as one atomic layer deposition cycle. After one atomic layer deposition cycle is completed, the sample is taken out from the reaction chamber to obtain catalyst G.
[0111] In the obtained catalyst G, the Pd nanoparticles are highly dispersed on the molecular sieve, and the Pd metal particles with a particle size of 2.5-3.5 nm account for 92% of all the Pd metal particles. The Pd metal loading measured by ICP-OES is 0.2 wt.%.
[0112] [Examples 8-14]
[0113] Take the Pd / SCM-1 molecular sieve catalyst synthesized in Examples 1-7 respectively, and carry out benzene hydroalkylation reaction in a closed reactor. 0.3g of the Pd / SCM-1 molecular sieve catalyst and benzene in the above Examples 1-7 are added to a high-pressure reactor with magnetic stirring, and hydrogen is introduced for replacement three times, and then hydrogen is filled to a certain pressure and sealed. The reaction conditions are: reaction temperature 150°C, hydrogen pressure 2.0MPa, hydrogen / benzene molar ratio 1.5, benzene / catalyst mass ratio 50, and reaction time 4 hours. The product in the reaction solution is quantitatively analyzed by gas chromatography. The selectivity of the catalytic product is shown in Table 1.
[0114] [Comparative Example 1]
[0115] Compared with the preparation of hydrogen-type SCM-1 molecular sieve in Example 1, the reaction conditions and material ratios are the same as in Example 1, except that dicyclohexylamine is not added, and the final material ratio (molar ratio) is:
[0116] SiO2 / Al2O3=30;
[0117] NaOH / SiO2=0.09;
[0118] Hexamethyleneimine / SiO2=0.25;
[0119] H2O / SiO2=32.
[0120] After the reaction materials are evenly mixed, they are transferred to a stainless steel reactor and crystallized at 150°C for 72 hours under stirring. After the crystallization reaction is completed, wash with deionized water several times until the pH value of the washing liquid reaches neutral, then dry at 80°C for 24 hours, and then transfer to a muffle furnace and calcine at 550°C in an air atmosphere for 6 hours to obtain a sodium-type SCM-1 molecular sieve. The sodium-type SCM-1 molecular sieve is exchanged with 0.5 mol / L NH4Cl solution at 45°C for ammonium ions for 2 hours, then centrifuged and washed. The ammonium ion exchange is repeated three times, and the obtained sample is dried at 80°C overnight, and calcined in air at 550°C for 6 hours to obtain a hydrogen-type molecular sieve sample DA, whose X-ray diffraction spectrum is shown in Figure 5 , which is significantly different from the hydrogen-type SCM-1 molecular sieve obtained in Example 1.
[0121] The molecular sieve powder DA was prepared by the same ALD metal deposition method as in Example 1 to obtain catalyst H.
[0122] In the obtained catalyst H, the Pd metal particles with a particle size of 2.5-3.5 nm accounted for 65% of all the Pd metal particles. The metal loading of Pd measured by ICP-OES was 0.3 wt.%.
[0123] [Comparative Example 2]
[0124] The preparation method of hydrogen-type SCM-1 molecular sieve is the same as that in Example 1.
[0125] Pd metal was loaded on SCM-1 by wet chemical method. 2 g hydrogen-type SCM-1 molecular sieve was dispersed in 60 mL deionized water, and then a concentration of 1.7×10 -3 6 mL of 1 mol / L chloropalladic acid solution (solid palladium chloride was dissolved in 1 M HCl in advance), referred to as solution A, was stirred at room temperature for 6 hours. In another reaction container, 25 mL of deionized water was added, followed by 70 mg of sodium borohydride, and the sodium borohydride aqueous solution was obtained after stirring and dissolving, referred to as solution B. Solution B was added dropwise to solution A, and the reaction was stirred at room temperature for 8 hours, centrifuged, and washed three times with deionized water. Catalyst I was obtained after drying at 80°C overnight. Its transmission electron microscope image is shown in Figure 3 .
[0126] In the obtained catalyst I, TEM results show that ( Figure 3 ), the Pd metal particles are extremely unevenly dispersed, and there are no Pd metal particles in the range of 2 to 4 nm. The Pd metal loading is 0.3 wt.% as measured by ICP-OES.
[0127] [Comparative Example 3]
[0128] The preparation method of hydrogen-type SCM-1 molecular sieve is the same as that in Example 1.
[0129] Pd metal was loaded on SCM-1 by wet chemical method. 2 g hydrogen-type SCM-1 molecular sieve was dispersed in 60 mL deionized water, and then a concentration of 1.7×10 -3 6 mL of 1 mol / L chloropalladic acid solution (solid palladium chloride was dissolved in 1 mol / L HCl in advance) was stirred at room temperature for 6 hours. The reaction temperature was then raised to 70°C and stirring was continued until the liquid was completely evaporated. The obtained powder solid was placed in a 10% H2 / Ar mixed gas, the temperature was programmed to 300°C, and the reaction was carried out for 2 hours to obtain catalyst J. Its transmission electron microscopy image is shown in Figure 4 .
[0130] In the obtained catalyst J, TEM results showed ( Figure 4 ), the Pd metal particles are extremely unevenly dispersed, and there are no Pd metal particles in the range of 2 to 4 nm. The Pd metal loading is 0.3 wt.% as measured by ICP-OES.
[0131] [Comparative Example 4]
[0132] The preparation method of hydrogen-type SCM-1 molecular sieve is the same as that in Example 1.
[0133] The method for depositing Pd metal on the hydrogen-type SCM-1 molecular sieve is the same as that in Example 1, except that the introduction time of the Pd(hfac)2 precursor and formaldehyde is extended to 2700 seconds and 2700 seconds, respectively, to obtain catalyst K.
[0134] In the obtained catalyst K, the Pd metal particles with a particle size of 2.5-3.5 nm accounted for 63% of all the Pd metal particles. The metal loading of Pd measured by ICP-OES was 0.6 wt.%.
[0135] [Comparative Example 5]
[0136] The preparation method of hydrogen-type SCM-1 molecular sieve is the same as that in Example 1.
[0137] The deposition method of Pd metal on hydrogen-type SCM-1 molecular sieve is the same as that in Example 1, except that the introduction time of Pd(hfac)2 precursor and formaldehyde is shortened to 500 seconds and 500 seconds, respectively, to obtain catalyst L. In this catalyst, effective metal deposition cannot be achieved, Pd metal particles with a particle size between 2.5 and 3.5 nm cannot be observed, and due to the extremely low content of the metal component, there is basically no activity.
[0138] [Comparative Examples 6-10]
[0139] Similar to Examples 8-14, the catalyst materials synthesized in Comparative Examples 1-5 were used to carry out catalytic reaction of benzene hydroalkylation. The selectivity of catalytic products is shown in Table 1.
[0140] Table 1 Catalyst performance results of Examples 8-14 and Comparative Examples 6-10
[0141]
[0142]
[0143] Table 2 Properties of SCM-1 molecular sieves obtained in each example
[0144] Molecular sieve number Average thickness / nm <![CDATA[External specific surface area / (m 2 / g)]]> Example 1 A 9.0 120 Example 2 B 10.0 100 Example 3 C 9.5 115 Example 4 D 12 95 Example 5 E 8.5 125 Comparative Example 1 DA 22 50
[0145] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A Pd / SCM-1 molecular sieve catalyst, characterized in that: The catalyst comprises SCM-1 molecular sieve and metal component Pd. On the surface of the catalyst, Pd metal particles with a particle size of 2-4 nm account for more than 85% of all Pd metal particles.
2. The catalyst according to claim 1, characterized in that In the SCM-1 molecular sieve, the crystals are nanosheet-like in morphology, and the thickness of the crystals is not higher than 15 nm, preferably 2 to 12 nm, and more preferably 8 to 10 nm; And / or, the external specific surface area of the SCM-1 molecular sieve is not less than 150m 2 / g, preferably 150 to 250 m 2 / g.
3. The catalyst according to claim 1, characterized in that Based on the weight of the catalyst, the content of the metal component Pd as an element is 0.01% to 5.0%, preferably 0.1% to 2.0%, and the rest is SCM-1 molecular sieve.
4. The catalyst according to claim 1, characterized in that On the surface of the catalyst, Pd metal particles with a particle size of 2.5 to 3.5 nm account for more than 90% of all Pd metal particles.
5. The method for preparing the Pd / SCM-1 molecular sieve catalyst according to any one of claims 1 to 4, comprising the following steps: (1) palladium source vapor contacts with SCM-1 molecular sieve for reaction; (2) purging the product obtained in step (1) for the first time with an inert gas; (3) contacting the product after purging in step (2) with a reducing agent to react; (4) The product obtained in step (3) is purged for a second time with an inert gas to obtain the Pd / SCM-1 molecular sieve catalyst.
6. The preparation method according to claim 5, characterized in that: The palladium source is at least one of bis(hexafluoroacetylacetonate)palladium (Pd(hfac)2), (2,2,6,6-tetramethyl-3,5-heptanedione)palladium, and acetylacetonate palladium; the reducing agent is at least one of formaldehyde and hydrogen.
7. The preparation method according to claim 5, characterized in that: In step (1), the reaction temperature is 80 to 300° C., preferably 120 to 250° C.; the reaction time is no more than 2000 seconds, preferably 800 to 1800 seconds; And / or, in step (3), the reaction time is no longer than 2000 seconds, preferably 800 to 1800 seconds.
8. The preparation method according to claim 5, characterized in that: In step (2), the first purge time is 500 to 800 seconds; And / or, in step (4), the second purge time is 500 to 800 seconds.
9. Use of the Pd / SCM-1 molecular sieve catalyst according to any one of claims 1 to 4 in a catalytic reaction of benzene hydroalkylation.
10. The use according to claim 9, characterized in that: The reaction conditions are: reaction temperature of 150-250° C., hydrogen pressure of 1.0-4.0 MPa, hydrogen / benzene molar ratio of 0.5-2.0, and benzene / catalyst mass ratio of 40-60.
Citation Information
Patent Citations
Preparation method of binderless molecular sieve catalyst
CN107511168A
Hierarchical pore molecular sieve supported metal catalyst as well as regulation and control method and application thereof
CN113275033A
Supported metal catalyst, preparation method and application thereof
CN113522276A
Alkylation reaction method and application thereof
CN113880682A
Hydroalkylation catalyst as well as preparation method and application thereof
CN114130421A
